Sport activity and cultural integration of international students in Universiti Putra Malaysia - Mohd Khalid, Noraseela; Yusof, Aminuddin; M. Shah, Parilah (Sucharitha Publications, 2016)
The aim of the study is to examine sport participation as a vehicle for cultural integration of international students at University Putra Malaysia (UPM). A total of 199 subjects were selected for the study. The Sport and Cultural Identity Scale (SCIS) developed by Allen (2010) was used to collect data. The instruments consist of 20 items measuring cultural maintenance and adaptation of to multicultural environment through sport. Even though the results show that sport participation among international students in UPM does not affect either their cultural maintenance or adaption to a multicultural environment, the mean score for the cultural adaptation is higher than the mean score for cultural maintenance with suggests that the subjects perceived opportunities for adapting a multicultural environment through sport were more important than for the cultural maintenance through sport.